No One Too Old to Learn: Managing Elder’s Lifelong Learning for Life Quality - Niyomsilp, Eksiri (วารสารวิจัยมหาวิทยาลัยเวสเทิร์น มนุษยศาสตร์และสังคมศาสตร์, 2024)
The context of this research is the discussion in “No One Too Old to Learn” in the content of managing elders’ lifelong learning to pursue the quality of life. Therefore, the research objectives aim to find problems scientifically using analytic and synthetic systemic and modeling skills, apply the knowledge of comprehensive analysis, and show a solid general knowledge of philosophy and scientific research methodology. The goal of the qualitative research methodology, known as the "inductive approach," is to investigate the application of the Critical Discourse Analysis technique by moving from the specific to the general. As a result, most significant contributors agree that the primary similarities between the two are in their approaches to human life education. Furthermore, the primary distinction lies in the global concept for educational sustainability and the personal or principled notion of lifelong learning patterns. Adhere to the same mainstream for both educational types. distinct topics of educational sustainability and lifelong learning that are relevant to older adults’ acceptable quality of life.